Potential for Gossypol Toxicity When Feeding Whole Cottonseed to Beef Cattle - Robert O. Myer; Lee R. McDowell (EDIS)
The feeding of whole cottonseed to beef cattle has increased over the last decade due to increased local cotton production. Whole cottonseed is a good source of both protein and energy for beef cattle rations. However, one should be aware of potential gossypol toxicity when feeding cottonseed. This document is AN130, one of a series of the Animal Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date April 2003.